PRAME-AS lncRNA, regulated by MZF1, modulates PRAME expression and cell stemness - Zahra Hosseininia; Hesam Dehghani (PLoS ONE, 2025)
PRAME is a member of the large cancer-testis antigens (CTA). In normal tissues, PRAME is mainly expressed in the testis. However, low levels of PRAME transcript are detected in the endometrium, ovary, and adrenal glands. Due to the tumor‐restricted expression of PRAME, some of its regulatory factors have been investigated; however, the role of lncRNAs remains unclear. In this study, we ablated the PRAME-AS gene and investigated the effects on PRAME expression, cell proliferation, migration, viability, and anchorage-independent growth. We further manipulated PRAME-AS expression through MZF1 overexpression and hypermethylation of its upstream regulatory region. Additionally, we assessed the ability of the PRAME locus regulatory region to drive PRAME-AS lncRNA transcription. Our findings show that PRAME-AS gene knockout diminishes PRAME transcript levels by about 37%. The PRAME-AS knockout cells showed a decrease in migration, proliferation, stemness, and viability. We discovered that MZF1 induces PRAME expression approximately twofold and increases PRAME-AS transcript levels by more than threefold. We found that hypermethylation of the upstream regulatory sequence of PRAME-AS results in an approximately 50% reduction in PRAME transcripts and an 18.5% decrease in PRAME-AS transcript levels. Moreover, based on our EGFP reporter assay, we conclude that the regulatory region of the PRAME locus—without PRAME transcription—is insufficient to drive transcription of PRAME-AS in the antisense direction. Taken together, our data support the conclusion that PRAME-AS lncRNA acts as a regulator of PRAME transcript levels, and that MZF1—and the methylation status of a shared CpG island— influence the expression of both genes.